A proposed media program for the College of Education, Pitsanuloke, Thailand - Metta, Chongchareon 1949-
A proposal media for the College of Education, Pitsanuloke, Thailand was designed in this study. The proposal for a desirable and workable media program for the college was based on the following principles: analysis of the practices and trends governing the organization and administration of media program, and the development on the basis on such analysis, principles and analysis of the present media program of the College of Education, Pitsanuloke.